(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Report on the campaign of year 2004 in the Sanctuary of the Deus Lar Berobreus in Monte de O Facho. The extension of the excavation area took to the finding of new altars to the divinity and its respective locations, its extension until the zone of castrum detected new structures, mainly of circular houses. The sacred area seems limited by the passage of the access road 1. The chronology is confirmed, by which the castrum becomes abandoned during first half of the s. I d.C., and the Sanctuary, nevertheless, does not arise before the s. III d.C., and survives until end of the s. IV d.C or principles of the s. V d.C.